1985
DOI: 10.1017/s0024282985000354
|View full text |Cite
|
Sign up to set email alerts
|

The Hyphomycetous Anamorph of Coniocybe Furfuracea

Abstract: Under favourable climatic conditions the mycobiont of Coniocybe furfuracea bears masses of conidia in chains on macronematous conidiophores. The same type of conidia were also formed by axenically grown mycobionts which had been isolated from single ascospores. Germinating conidia were found on the thalli. Coniocybe furfuracea is one of the very few lichen mycobionts so far known with a teleomorph and hyphomycetous anamorph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Pycnidia known with certainty only from axenic cultures of some Chaenotheca species (Tibell, 1993, 1997); simple, Asterophoma ‐like. Simple hyphomycetous anamorphs have been obtained in axenic cultures of several Chaenotheca species but have also been observed in the field (Honegger, 1985; Tibell, 1993, 1997). Pulvinic and vulpinic acid derivates occur as a pruina or rarely within the thallus, β‐orcinol depsides atranorin, baeomycesic and squamatic acid occur in the thallus of some species and pseudoplacodiolic acid occurs in one species (Tibell, 1999).…”
Section: Taxonomymentioning
confidence: 99%
“…Pycnidia known with certainty only from axenic cultures of some Chaenotheca species (Tibell, 1993, 1997); simple, Asterophoma ‐like. Simple hyphomycetous anamorphs have been obtained in axenic cultures of several Chaenotheca species but have also been observed in the field (Honegger, 1985; Tibell, 1993, 1997). Pulvinic and vulpinic acid derivates occur as a pruina or rarely within the thallus, β‐orcinol depsides atranorin, baeomycesic and squamatic acid occur in the thallus of some species and pseudoplacodiolic acid occurs in one species (Tibell, 1999).…”
Section: Taxonomymentioning
confidence: 99%
“…Conidia occur in field-collected material (Honegger, 1985), in cultures of the mycobiont of lichenized species (Tibell, 1993b) and in axenic cultures of nonlichenized species (Tibell, 1990(Tibell, , 199 1, 1993aTibell & Constantinescu, 199 1). I have suggested that these may function as asexual propagules (Tibell, 1990(Tibell, , 1993, which possibly propagate the species in a non-lichenized cycle in nature. The conidia are unlikely to function in long distance dispersal as they are generally thin-walled and non-pigmented and are thus ill-equipped to survive prolonged desiccation and intense UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Hyphomycetous anamorphs, though possibly often overlooked, must still be considered rare among the lichen-forming fungi with known teleomorphs (see short reviews in Vobis & Hawksworth 1981, and the recent additions by Honegger 1985, Coppins & Purvis 1987, Ott 1987.…”
Section: Historical Introductionmentioning
confidence: 99%